Investigation of the Molecular Mechanism of Coagulopathy in Severe and Critical Patients With COVID-19 - Elieh Ali Komi, Daniel; Rahimi, Yaghoub; Asghari, Rahim; Jafari, Reza; Rasouli, Javad; Mohebalizadeh, Mehdi; Abbasi, Ata; Nejadrahim, Rahim; Rezazadeh, Farzin; Shafiei-Irannejad, Vahid (Frontiers in Immunology, 2021)
Coagulopathy is a frequently reported finding in the pathology of COVID-19, however, the molecular mechanism, involved coagulation factors, and the role of regulatory proteins in homeostasis are not fully investigated. We explored the dynamic changes of nine coagulation tests in patients and controls to propose a molecular mechanism for COVID-19-associated coagulopathy. Coagulation tests including PT, PTT, fibrinogen (FIB), lupus anticoagulant (LAC), Protein C, and S, Antithrombin III (ATIII), D-Dimer, and fibrin degradation products (FDP) were performed on plasma collected from 105 individuals (35 critical and 35 severe patients, and 35 healthy controls). There was a statically significant difference when the results of the critical (CRT) and/or severe (SVR) group for the following tests compared to the controls (CRL)group: PTCRT (15.014) and PTSVR (13.846) (PTCRL 13.383, p<0.001), PTTCRT (42.923) and PTTSVR (37.8) (PTTCRL 36.494, p<0.001), LACCRT (49.414) and LACSVR (47.046) (LACCRL 40.763, p<0.001), FIBCRT (537.66) and FIBSVR (480.29) (FIBCRL 283.57, p<0.001), ProCCRT (85.57%) and ProCSVR (99.34%) (ProCCRL 94.31%, p=0.04), ProSCRT (62.91%) and ProSSVR (65.06%) (ProSCRL 75.03%, p<0.001), D-Dimer (p<0.0001, χ2=34.812), and FDP (p<0.002 χ2=15.205). No significant association was found in ATIII results in groups (ATIIICRT (95.71%) and ATIIISVR (99.63%) (ATIIICRL 98.74%, p=0.321). D-Dimer, FIB, PT, PTT, LAC, Protein S, FDP, and Protein C (ordered according to P values) have significance in prognosis of patients. Disruptions in homeostasis in Protein C (and S): VIII/VIIIa and V/Va axes, probably play a role in COVID-19-associated coagulopathy.